Ovidius painted and printed. The influence of Metamorphoses illustrations on two friezes in Marca di Ancona - Francesca Casamassima (Il Capitale Culturale: Studies on the Value of Cultural Heritage, 2024)
This paper delves into the iconography of two friezes adorning the rooms of two palazzi located in the Marca di Ancona, a peripheral region within the Papal States. All the scenes portrayed in the two friezes are inspired by the Ovid’s Metamorphoses. The purpose of this paper is to demonstrate the influence of the illustrations found in the vernacular translations of the Metamorphoses, which were spread around Italy from the end of the 15th century. Additionally, it aims to explore the impact of prints that circulated freely, reproducing models from renowned artists like Michelangelo. These prints disseminated iconographies throughout Italy, making them known even in the provincial areas. The clients used them in an attempt to adapt their taste to the prevailing fashions of the big centers. Meanwhile the artists – unable to rival their counterparts from the centers – were provided with models which, in some instances, they closely adhered to.